Efektivitas Project Based Learning Berbasis Ekopedagogik dalam Meningkatkan Kemampuan Berpikir Kritis Siswa SMP pada Materi Pencemaran Air: (The Effectiveness of Eco-Pedagogical Project-Based Learning in Improving Junior High School Students’ Critical Thinking Skills on Water Pollution Topics) - Septia Tri Andini, Sheni; Ratnasari, Jujun; Suhendar, Suhendar (BIODIK, 2026)
This study aimed to determine the effect of the Project Based Learning model integrated with an ecopedagogical approach on junior high school students' critical thinking skills in the topic of water pollution. This study employed a quasi-experimental method using a pretest–posttest control group design. The research instrument was a critical thinking skills test administered to the experimental and control classes. The results showed that the experimental class achieved an N-Gain score of 0.76 (high category), while the control class achieved 0.48 (moderate category). The Mann–Whitney U test yielded an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), indicating a significant difference in the improvement of critical thinking skills between the two classes. Therefore, the Project Based Learning model integrated with an ecopedagogical approach had a significant effect on improving students' critical thinking skills in the topic of water pollution. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh model Project Based Learning berbasis ekopedagogik terhadap kemampuan berpikir kritis siswa SMP pada materi pencemaran air. Penelitian ini menggunakan metode quasi-experimental dengan desain pretest–posttest control group design. Instrumen penelitian berupa tes kemampuan berpikir kritis yang diberikan kepada kelas eksperimen dan kelas kontrol. Hasil penelitian menunjukkan bahwa nilai N-Gain kelas eksperimen sebesar 0,76 (kategori tinggi), sedangkan kelas kontrol sebesar 0,48 (kategori sedang). Hasil uji Mann–Whitney U menunjukkan nilai Asymp. Sig. (2-tailed) sebesar 0,000 (p < 0,05), yang menunjukkan adanya perbedaan peningkatan kemampuan berpikir kritis yang signifikan antara kedua kelas. Dengan demikian, model Project Based Learning berbasis ekopedagogik berpengaruh signifikan terhadap kemampuan berpikir kritis siswa pada materi pencemaran air.